In Yosemite - Smirnova, Olga (project baikal, 2017)
The article tells about the author's visit to Yosemite National Park, USA. It describes how the territory is used for sports and what facilities are provided for the guests.
Keywords: Yosemite; Half-Dome; El-Capitan; BASE jumping; the Merced River; giant sequoias; wingsuit